Repeated valve replacement: approaches and devices (literature review) - K. Yu. Klyshnikov; E. A. Ovcharenko; A. N. Stasev; L. S. Barbarash (Кардиоваскулярная терапия и профилактика, 2023)
Bioprosthetic valve dysfunction represent a serious drawback that limits the wider clinical use of these medical devices for valvular heart disease surgery. Modern studies describe the view of pathophysiologists on this problem as a multifactorial multi-stage process that causes irreversible changes in bioprosthesis components, ultimately leading to its dysfunction. However, in addition to under- standing the causes and manifestations of prosthetic valve dys- function, an applied question arises about the treatment strategies — determining the most attenuated and accessible low-risk method/ device. The aim of this review was to analyze and systematize current literature data on methods and designs used in repeated surgical and transcatheter interventions on heart valves.